K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

31 tháng 1 2023

\(x^2+4x+8=x^2+2.2x+4+4=\left(x+2\right)^2+4\\ \left(x+2\right)^2\ge0\forall x\\ =>\left(x+2\right)^2+4>4\left(>0\right)\forall x\\ =>x^2+4x+8>0\left(\forall x\right)\)

31 tháng 1 2023

\(Ta\) \(có:\) \(x^2+4x+8\)

\(=x^2+4x+4+4\)

\(=\left(x+2\right)^2+4\)

\(mà:\) \(\left(x+2\right)^2\ge0\)

\(\Rightarrow\left(x+2\right)^2+4>0\) \(hay\) \(x^2+4x+8>0\) với mọi x

30 tháng 1 2023

P = (a + b + c)3 - 4(a3 + b3 + c3) - 12abc

= (a + b + c)3 - 4(a3 + b3 + c3 + 3abc) 

= (a + b + c)3 - 8c3 - 4(a3 + b3 - c3 + 3abc) 

= (a + b + c)3 - (2c)3 - 4(a3 + b3 - c3 + 3abc) 

Có (a + b + c)3 - (2c)3 

= (a + b - c)[(a + b + c)2 + (a + b + c).2c + 4c2]

= (a + b - c)(a2 + b2 + c2 + 2ab + 2bc + 2ca + 2ac + 2bc + 2c2 + 4c2)

= (a + b - c)(a2 + b2 + 7c2 + 4bc + 4ac + 2ba)

Lại có a3 + b3 - c3 + 3abc

 = (a + b)3 - c3 - 3ab(a + b) + 3abc

= (a + b - c)[(a + b)2 + (a + b)c + c2 - 3ab]

= (a + b - c)(a2 + b2 + c2 + ac + bc - ab) 

Khi đó P = (a + b - c)(a2 + b2 + 7c2 + 4bc + 4ac + 2ba) - 4(a + b - c)(a2 + b2 + c2 + ac + bc - ab) 

= (a + b - c)(-3a2 - 3b2 + 3c2 + 6ba)

= 3(a + b - c)(- a2 - b2 + 2ab + c2)

= 3(a + b - c)[c2 - (a - b)2]

= 3(a + b - c)(a + c - b)(c - a + b) 

Nếu P < 0 thì  3(a + b - c)(a + c - b)(c - a + b)  < 0

<=>  (a + b - c)(a + c - b)(c + b - a) < 0

=> Có ít nhất một hạng tử trái dấu với 2 hạng tử còn lại

Với a,b,c > 0

Giả sử \(\left\{{}\begin{matrix}a+b-c< 0\\a+c-b>0\\b+c-a>0\end{matrix}\right.\) => a;b;c không là 3 cạnh tam giác 

hoặc \(\left\{{}\begin{matrix}a+b-c>0\\b+c-a< 0\\a+c-b< 0\end{matrix}\right.\) cũng tương tự

Vậy a,b,c không là 3 cạnh tam giác 

30 tháng 1 2023

Không kết luận được bất cứ điều gì nếu không có thêm điều kiện a;b;c là các số dương

30 tháng 1 2023

\(\dfrac{x-241}{17}+\dfrac{x-220}{19}+\dfrac{x-195}{21}+\dfrac{x-166}{23}=10\)

\(\Leftrightarrow\dfrac{x-241}{17}+\dfrac{x-220}{19}+\dfrac{x-195}{21}+\dfrac{x-166}{23}-10=0\)

\(\Leftrightarrow(\dfrac{x-241}{17}-1)+(\dfrac{x-220}{19}-2)+(\dfrac{x-195}{21}-3)+(\dfrac{x-166}{23}-4)=0\)

\(\Leftrightarrow\dfrac{x-258}{17}+\dfrac{x-258}{19}+\dfrac{x-258}{21}+\dfrac{x-258}{23}=0\)

\(\Leftrightarrow\left(x-258\right)\left(\dfrac{1}{17}+\dfrac{1}{19}+\dfrac{1}{21}+\dfrac{1}{23}\right)=0\)

\(Do\) \(\left(\dfrac{1}{17}+\dfrac{1}{19}+\dfrac{1}{21}+\dfrac{1}{23}\right)\ne0\) \(nên\) \(để\) \(gt=0\)

\(\Leftrightarrow x-258=0\)

\(\Leftrightarrow x=258\)

\(Vậy...\)

29 tháng 1 2023

\(a.\) \(ax^2-a^2x-x+a\)

\(=\left(ax^2-a^2x\right)-\left(x-a\right)\)

\(=ax\left(x-a\right)-\left(x-a\right)\)

\(=\left(ax-1\right)\left(x-a\right)\)

\(b.\) \(18x^3-12x^2+2x\)

\(=2x\left(9x^2-6x+1\right)\)

\(=2x\left(3x-1\right)^2\)

\(c.\) \(x^3-5x^2-4x+20\)

\(=\left(x^3-5x^2\right)-\left(4x-20\right)\)

\(=x^2\left(x-5\right)-4\left(x-5\right)\)

\(=\left(x^2-4\right)\left(x-5\right)\)

\(=\left(x-2\right)\left(x+2\right)\left(x-5\right)\)

\(d.\) \(\left(x+7\right)\left(x+15\right)+15\)

\(=x^2+15x+7x+105+15\)

\(=x^2+22x+120\)

\(=\left(x+10\right)\left(x+12\right)\)

29 tháng 1 2023

loading...  

29 tháng 1 2023

34. A tourist travels more cheaply than a business person.

35. We have learned English for 5 years.

36. My marks are worse than Jack's.
 

29 tháng 1 2023

 37. We cannot swim in this part of the river because the water is highly polluted. 

38. Mr. Minh has been admired since he dedicated all his life to protecting environment.

39. Lan was sick so she didn't go to school 

??? 40.A lot of Viet Namese people have the custom to buy sugar cane on New Year's Eve 

 

29 tháng 1 2023

37. We cannot swim in this part of the river because the water is highly polluted.

29 tháng 1 2023

9.The house caught fire while they were sleeping.

29 tháng 1 2023

9 The house were catching fire while they were sleeping 

28 tháng 1 2023

\(A=\dfrac{a}{ab+a+1}+\dfrac{b}{bc+b+1}+\dfrac{c}{ac+c+1}\)

\(A=\dfrac{a^2bc}{ab+a^2bc+abc}+\dfrac{b}{bc+b+abc}+\dfrac{c}{ac+c+1}\)

\(A=\dfrac{a^2bc}{ab\left(1+ac+c\right)}+\dfrac{b}{b\left(c+1+ac\right)}+\dfrac{c}{ac+c+1}\)

\(A=\dfrac{ac+1+c}{ac+c+1}\)

\(A=1\)

 

28 tháng 1 2023

\(A=\dfrac{ab}{ab+a+1}+\dfrac{bc}{bc+b+1}+\dfrac{ca}{ca+c+1}\)

\(A=\dfrac{abc}{abc+ac+c}+\dfrac{bc}{bc+b+abc}+\dfrac{ca}{ca+c+1}\)

\(A=\dfrac{1}{1+ac+c}+\dfrac{c}{c+1+ac}+\dfrac{ca}{ca+c+1}\)

\(A=1\)